2015
DOI: 10.1377/hlthaff.2014.1358
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Medicaid Adult Dental Coverage In California Led To Increased Dental Emergency Visits And Associated Costs

Abstract: Dental coverage for adults is an elective benefit under Medicaid. As a result of budget constraints, California Medicaid eliminated its comprehensive adult dental coverage in July 2009. We examined the impact of this policy change on emergency department (ED) visits by Medicaid-enrolled adults for dental problems in the period 2006-11. We found that the policy change led to a significant and immediate increase in dental ED use, amounting to more than 1,800 additional dental ED visits per year. Young adults, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 19 publications
(18 reference statements)
3
69
0
Order By: Relevance
“…In general, it has been recognized since the 1960s that low-income individuals have more missing teeth with a higher prevalence and severity of periodontal diseases [11]. Epidemiological studies have suggested that income is associated with disparities in preventive dental care and regular checkup rates, and that low-income individuals are more likely to visit providers for emergency or temporary care than their higher-income counterparts [5825]. A study by Lee et al [7] concluded that more people need periodontal scaling among those with lower levels of income in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it has been recognized since the 1960s that low-income individuals have more missing teeth with a higher prevalence and severity of periodontal diseases [11]. Epidemiological studies have suggested that income is associated with disparities in preventive dental care and regular checkup rates, and that low-income individuals are more likely to visit providers for emergency or temporary care than their higher-income counterparts [5825]. A study by Lee et al [7] concluded that more people need periodontal scaling among those with lower levels of income in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the dental benefits are being offered under an innovative “earned benefits model” to this newly eligible Medicaid population. Many of the new Medicaid enrollees are expected to be young adults, who had limited dental coverage in the past, and is the group that has been shown to be most likely to visit EDs for dental problems . Although several states have reported on ED visits for dental problems , very few states have the ability to examine revisits to the ED for dental problems by the same person, due to data limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the new Medicaid enrollees are expected to be young adults, who had limited dental coverage in the past, and is the group that has been shown to be most likely to visit EDs for dental problems . Although several states have reported on ED visits for dental problems , very few states have the ability to examine revisits to the ED for dental problems by the same person, due to data limitations. The purpose of this study was to: Compare patient characteristics associated with having an ED visit for NTDCs to those associated with other ED visits. Examine characteristics associated with having multiple re‐visits to the ED for NTDCs. Compare charges associated with ED visits for NTDCs and other conditions. …”
Section: Introductionmentioning
confidence: 99%
“…In California, the elimination of dental benefits for Medicaid adult enrollees led to an immediate and significant increase in dental ED visits by Medicaid-enrolled adults (4). Similarly, the elimination of adult Medicaid dental benefits in Oregon in 2003 resulted in an increase in dental-related ED use as well as an increase in the incidence of unmet oral health needs among adult beneficiaries (5).…”
Section: Introductionmentioning
confidence: 99%